FINANCIAL PERFORMANCE ANALYSIS (CASE STUDY OF JOINT BUSINESS COOPERATIVE SAVINGS AND LOANS IN TEMBILAHAN) - ELSA LAURA RISKY RAHMADANI; SM. GUNTUR; NELVA SISKAWATI (Indragiri Research Center (ingreat), 2023)
This research was carried out at the Joint Business Cooperative in 2017-2021. This research aims to determine the financial performance of the Joint Venture Savings and Loans Cooperative in 2017-2021. The type of research used is quantitative descriptive analysis. The data processed is financial report data for 2017-2021. The data analysis technique used is financial ratio analysis, namely liquidity ratios, solvency ratios and profitability ratios. The population and sample in this research are all financial reports of Joint Business Cooperatives for 2017-2021. The results of this research show the Liquidity Ratio of current ratio the Joint Venture KSP Usaha Bersama is considered good, the Solvency Ratio of debt to asset ratio and debt to equity ratio assessed as good, and the Profitability Ratio of Economic Profitability and Own Capital Profitability is assessed as not good.